The Burden of Stroke in Kurdistan Province, Iran From 2011 to 2017 - Shahram Moradi; Ghobad Moradi; Bakhtiar Piroozi (Korean Society for Preventive Medicine, 2021)
Objectives The aim of this study was to calculate the burden of stroke in Kurdistan Province, Iran between 2011 and 2017. Methods Incidence data extracted from the hospital information system of Kurdistan Province and death data extracted from the system of registration and classification of causes of death were used in a cross-sectional study. The World Health Organization method was used to calculate disability-adjusted life years (DALYs). Results The burden of stroke increased from 2453.44 DALYs in 2011 to 5269.68 in 2017, the years of life lost increased from 2381.57 in 2011 to 5109.68 in 2017, and the years of healthy life lost due to disability increased from 71.87 in 2011 to 159.99 in 2017. The DALYs of ischaemic stroke exceeded those of haemorrhagic stroke. The burden of disease, new cases, and deaths doubled during the study period. The age-standardised incidence rate of ischaemic stroke and haemorrhagic stroke in 2017 was 21.72 and 20.72 per 100 000 population, respectively. Conclusions The burden of stroke is increasing in Kurdistan Province. Since health services in Iran are based on treatment, steps are needed to revise the current treatment services for stroke and to improve the quality of services. Policy-makers and managers of the health system need to plan to reduce the known risk factors for stroke in the community. In addition to preventive interventions, efficient and up-to-date interventions are recommended for the rapid diagnosis and treatment of stroke patients in hospitals. Along with therapeutic interventions, preventive interventions can help reduce the stroke burden.